MOTIVASI KEWIRAUSAHAAN ANAK PANTI ASUHAN HIDAYATUL MUSLIM DESA UJUNGBATU KABUPATEN ROKAN HULU - Wulandari, Riana; Ayub, Daeng Ayub; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to study the Motivation of Entrepreneurship in the Hidayatul Muslim Orphanage in Ujungbatu Village. The formulation of the problem in this study is the problem of Entrepreneurship Motivation of Hidayatul Muslim Orphanage in Ujungbatu Village. This study consists of 4 indicators, according to the opinion of Peter F Ducker and Suryana. The population in this study amounted to 46 people. The sample of this study uses the Simple Random Sampling technique, which is taking a sample from a population that is done randomly without regard to strata that exist in that population (Sugiyono, 2011: 57). The data collection technique in this study was a questionnaire technique, which captured 40 acknowledgments. Data obtained from respondents obtained 20 people for the trial sample and 40 people for the study sample. After the questionnaire was tested, there were 4 invalid statements, and the researchers sent invalid statements. Based on the average results of the average value for the entrepreneurship motivation variable of the Children of Hidaaytul Muslim Orphanage in Ujungbatu Village, it is classified as high with Mean 4.15 and SD 0.30. As an interpretation obtained for each indicator of entrepreneurship Motivation, the children of the Hidayatul Muslim Orphanage in Ujungbatu Village are all classified as high. So, seen the most dominant of these 4 indicators is Spirit.Key Words: Motivation, Entrepreneurship, Orphanage